PENGARUH BAHASA PROKEM TERHADAP PEMBENTUKAN KARAKTER BERBAHASA MAHASISWA DALAM MEDIA SOSIAL - Muhammad Abdul Piki; Teti Sobari (IKIP Siliwangi, 2020)
Communication is carried out by many people, including students, not only directly, but can also be done through social media. Prokem language is also often used by students. This causes students difficulties in communicating formally and indirectly students reduce the character of language in themselves. The decline in language character is not only done face-to-face, but in social media too it has already been done. Thus, the objectives of this study are as follows: 1) to find out the extent to which the prokem language is used by students, 2) to describe the results of prokem language with a questionnaire via google form. 3) find out the impact of using prokem language on students. This study used descriptive qualitative method. Data collection techniques in the form of a questionnaire. The research respondents were carried out by 59 students. The results of this study indicate that 1) prokem language is accustomed to being used among students, 2) prokem language has been widely used in daily communication, 3) prokem language is not good enough to be used in formal situations or activities related to learning and in politeness of language is also lacking feasible, 4) prokem language among students is used on social media, both in conversation and making captions.